2008
DOI: 10.1161/strokeaha.107.497438
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of White-Matter Hyperintensities in Alzheimer Disease, Cerebral Amyloid Angiopathy, and Healthy Aging

Abstract: Background and Purpose-White-matter hyperintensities (WMHs) detected by magnetic resonance imaging are thought to represent the effects of cerebral small-vessel disease and neurodegenerative changes. We sought to determine whether the spatial distribution of WMHs discriminates between different disease groups and healthy aging individuals and whether these distributions are related to local cerebral perfusion patterns. Methods-We examined the pattern of WMHs by T2/fluid-attenuated inversion recovery-weighted m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
160
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(179 citation statements)
references
References 47 publications
(34 reference statements)
16
160
0
3
Order By: Relevance
“…However, WMHs primarily develop in regions with low perfusion, suggesting that low perfusion is involved in WMH conception. 21,22 Conceivably, tiny infarctions interact with low-grade hypoperfusion, for example, originating when perfusion in a small area drops below a certain threshold. Such low-grade hypoperfusion could be too small to measure with current techniques and only becomes apparent after WMHs develop due to tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, WMHs primarily develop in regions with low perfusion, suggesting that low perfusion is involved in WMH conception. 21,22 Conceivably, tiny infarctions interact with low-grade hypoperfusion, for example, originating when perfusion in a small area drops below a certain threshold. Such low-grade hypoperfusion could be too small to measure with current techniques and only becomes apparent after WMHs develop due to tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…20 WMHs primarily originate in physiologically poorly perfused areas (ie, the periventricular and deep WM), explaining how even a slight cerebral perfusion deficit could provoke low-grade ischemia in those regions associated with WMHs. 21,22 Low perfusion in NAWM has also been associated with subsequent WMH development. 23 While these findings seem to suggest that WMHs are related to a perfusion deficit extending beyond the WMHs, current evidence remains circumstantial.…”
mentioning
confidence: 99%
“…Therefore, dietary NO 3 Ϫ supplementation may have the potential to modify cerebrovascular physiology and enhance cognitive function. Indeed, Presley et al (63) recently reported that dietary nitrate improves regional white matter perfusion in older adults in areas of the brain that are involved in executive functioning and speculated that this may offset the influence of aging on cognitive decline and dementia (32).…”
mentioning
confidence: 99%
“…43,44 FreeSurfer is an automatic tool that estimates a number of regional brain volumes (e.g., hippocampus, amygdala, and thalamus) from T1-weighted MRI. Manual WMC volumetry on FLAIR images is also performed in the Gothenburg MCI study using the software MRIcron, employing a modified method used by Holland et al 45 To consistently analyze each participant series, a grayscale mapping of the brain tissue is performed in the image containing the quadrigeminal plate. After the manual segmentation, an image intensity thresholding is applied and the overlap between the manually segmented regions and the intensity thresholding is used as estimates of WMC volume.…”
Section: Neuropsychological Testsmentioning
confidence: 99%